TALAK PERSPEKTIF KESETARAAN GENDER: PERINTAH TUHAN MENERAPKAN EGALITER DI DALAM RUMAH TANGGA - Diana Farid; Muhammad Husni Abdulah Pakarti; Mohamad Hilal Nu’man; Hendriana Hendriana; Iffah Fathiah (Prodi Hukum Keluarga Islam (Ahwal Asy-Syakhsiyyah) Fakultas Syariah Unisba, 2023)
This article tries to discuss divorce from a gender perspective, this research arises from the understanding of a handful of Islamic societies regarding the use of divorce rights to break marriage ties. The belief that divorce is the authoritative right of men causes husbands to treat their wives as they please. So this is very contrary to gender equality and protection of women. This article aims to create an understanding of Divorce from a gender perspective. The method used in this article is library research with a qualitative form. Data was collected from articles in journals, books and other library materials which were then narrated. The results of the study found that divorce from a gender perspective is interpreted as equal rights between a husband and wife in filing for divorce, such as khuluk and fasahk.